Percutaneous Nephrolithotripsy in Morbidly Obese Patient: A Case Report - Fadhel Yusuf; Amr Elmekresh; Senthil Kumar; Fariborz Bagheri (Case Reports in Urology)
A 50-year old male patient with morbid obesity was admitted for removal of large staghorn calculi and multiple small stones in the left kidney. The patient was managed by Percutaneous Nephrolithotomy (PCNL). Surgery was carried out in prone position and Alken’s metal dilators were used for tract dilation. Alken dilators were inserted without any challenges, and the procedure was completed in a shorter span of time than anticipated with total operative time of 2 hours, including the change of positioning from lithotomy to prone. No intra-operative or post-operative complications were encountered. The patient has been followed up for 6 months post-operatively, without any complications or any evidence of stone recurrence.